LIFE AFTER HEMODIALYSIS - Santana, Mariela Beatriz Andrade; Silva, Denise Maria Guerreiro Vieira da; Lopes, Soraia Geraldo Rozza (My University, 2020)
ABSTRACT Objective: to know the problems people face as a consequence of chronic kidney disease and their hemodialysis treatment. Method: a qualitative, exploratory and descriptive study with 12 people who were undergoing hemodialysis in a reference hospital. Semi-structured interviews were carried out at the people's homes from September to December 2018. Data were analyzed according to directed content analysis, starting with identification of codes, which were later grouped into subcategories and categories. Results: people experienced significant changes in their lives after starting hemodialysis, presenting problems derived from treatment that were faced in order to maintain their lifestyle or resigning themselves to living abandoning aspects that gave them pleasure. The importance of maintaining power of will to continue treatment was appreciated, added to the acceptance process that was different for each person. Finally, a familiarity with death was evidenced due to frequent exposure to it through the death of hemodialysis colleagues, causing preparation for it. Conclusions: change in people's lives as a result of disease and treatment is a complex situation for which they must mobilize personal tools that entail great efforts, living an acceptance process that can take years. Attention by health professionals must achieve closeness, empathy, humanity in treatment to promote own resources that favor personal well-being.
Keywords: chronic kidney disease; renal dialysis; lifestyle; chronic disease; death